Experimental study of engine performance using a blend of RON 90 gasoline and fractionated gasoline equivalent from plastic pyrolysis oil - Bisrul Hapis Tambunan; Janter P. Simanjuntak; Sahala Siallagan; Bonaraja Purba; Rimbawati Rimbawati; Nurin Wahidah Mohd Zulkifli; Mohd Kamal Kamarulzaman (Universitas Mercu Buana, 2026)
This study investigated the performance and emission characteristics of a gasoline engine using a blend of commercial gasoline RON 90 and fractionated plastic pyrolysis oil (PPO). Almost all previous studies used unfractionated PPO in engine performance tests. The use of raw PPO in engine performance tests will result in poor engine performance, because the physicochemical properties of the fuel do not meet engine requirements and the ASTM D4814 standard (gasoline fuel properties standard). An innovative aspect of this study is that the raw PPO was first fractionated to separate the gasoline PPO fraction, the diesel PPO fraction, and other aromatic fractions. Gasoline-equivalent PPO was used in the engine performance test to ensure the fuel used met engine specifications. PPO is obtained from post-consumer plastic waste through a pyrolysis process, followed by fractionation to separate heavy fractions and complex aromatic compounds. Blends containing up to 40% fractionated PPO were tested to evaluate their effects on engine performance and emissions. Experimental results showed that the use of 40% PPO only reduced thermal efficiency 0.79%, which is very low compared to the results of previous studies. In terms of emissions, the use of a 40% fractionated PPO blend reduced CO emissions by 7%, reduced HC by 17%, and increased CO2 by 17%. The reduction in CO2 and HC emissions is an innovative aspect of this study. These findings differ from previous studies using raw PPO, which reported significant engine performance degradation and increased emissions due to poor combustion characteristics.